Diversitas dan Etno-ornitologi Burung Bernilai Ekonomis sebagai Bentuk Kearifan Lokal Masyarakat di Pasar Hobi, Toddoppuli, Makassar - Yunadia; Delfiah, Fila; Harun, Hadrian Rukmana; Zahara, Syahnas Ainun; Ningsih, Sulastri Ayu; Yanti, Widya; Nurhalisa, Ince St; Amrullah, Syarif Hidayat; Alir, Rahmat Fajrin (Universitas Islam Negeri Alauddin Makassar, 2024)
The diversity of species and the unique beauty values found in each bird cause many people to like birds. The high public interest in keeping birds encourages various contests and competitions. The relationship between humans and birds is called ethnoornithology. This research aims to determine the diversity or ethnoornithological diversity of economically valuable birds at the Toddopuli Hobby Market, Makassar. The methods used in this research are observation and in-depth interviews. The results obtained in this research are that there are doves with the highest percentage of birds in the hobby market, namely 32.26%. Meanwhile, the most expensive bird is the Bali starling, which has a price of 10 million rupiah. The most prominent family is the Columbidae family, with 857 individuals; the smallest is the Corvidae family, with one. Based on data obtained from 43 bird species, 13 are categorized as protected according to IUCN, CITES and PLHK. This research concludes that there are two protected birds according to PLKH, two bird types according to CITES Appendix II and one type Appendix l, as well as five types in the IUCN category; one type has Vulnerable (VU) status, three types have Endangered (EN) status, and one the type as Critically Endangered (CR) status. Most birds traded are still classified as Least Concern (LC). The majority of birds traded are in demand because of their singing.